Hypnoteaching dalam Pembelajaran Bahasa Arab - Lutfiyatun, Eka (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2023)
Arabic Learning faces problems in the post-pandemic period. Students experience demotivation in learning so that learning outcomes decrease. For this reason, innovation with the hypnoteaching method is needed to provide positive suggestions and motivations so as to arouse enthusiasm for learning Arabic. The purpose of this study is to describe how educators apply hypnoteaching in Arabic learning. The method used is descriptive analysis or literature review that produces descriptive data from various research results about the experience of educators in implementing hypnoteaching in Arabic learning. Hypnoteaching is carried out with six steps, namely self-motivation, pacing, leading, using positive words, giving praise, and modelling. Basically, hypnoteaching makes the learning environment comfortable and conducive for students so that learning outcomes are optimal.